Postremoval Geographies: Immigration Enforcement and Organized Crime on the U.S.–Mexico Border. Issue 4 (7th June 2021) - Slack, Jeremy; Martínez, Daniel E.
Abstract : What happens after deportation? What contexts must Mexican deportees navigate and contend with after removal from the United States? This article explores the challenges for people postremoval in Mexico, particularly by drawing on fieldwork conducted in Tamaulipas, which is home to the Zetas drug trafficking organization and the infamous massacre of seventy-two migrants. We argue that incidental exposure to violence and crime began as an implicit aspect of immigration enforcement and has grown into one of the central tenets of current policy. We take a feminist geopolitical approach to connect the postdeportation experiences of migrants to the policies of deportation, incarceration, and punishment levied against them by the U.S. government. Migrants, particularly those apprehended through the Criminal Alien Program, have been returned to Tamaulipas in concentrated numbers despite its violent reputation. The processes of criminalization have led to a system that prioritizes punishment for migrants, meaning that we cannot extricate experiences that occur after removal from enforcement measures that create those situations. These practices are directly connected to the current wave of policies aimed at stopping asylum seekers, including "metering, " where people are made to wait at the border to apply for asylum at the port of entry, and the Remain in Mexico program (otherwise known as the Migrant Protection Protocols). We argue that enforcement is more complex than "prevention through deterrence" narratives and exposure to nonstate violence in Mexico has slowly become a more integral part of enforcement plans.